2015
DOI: 10.1007/s11032-015-0372-8
|View full text |Cite
|
Sign up to set email alerts
|

Identification of maternal haploids of Nicotiana tabacum aided by transgenic expression of green fluorescent protein: evidence for chromosome elimination in the N. tabacum × N. africana interspecific cross

Abstract: The Nicotiana tabacum 9 N. africana cross is a semilethal cross, where greater than 99 % of progeny die in the cotyledonary stage due to an interspecific lethality reaction. The low frequencies of surviving plants are mixtures of maternal tobacco haploids and aneuploid F 1 hybrids. For effective use of surviving haploids in a breeding program, an efficient method is needed to distinguish them from aneuploid hybrids during the seedling stage. The first objective of this research was to investigate the use of N.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 50 publications
5
13
0
Order By: Relevance
“…Speci cally, 11 hybrid seedlings that had overcome lethality were obtained, and the frequency of appearance of hybrid seedlings that overcame lethality in this cross combination was calculated to be 8.5 x 10 -4 . This value was close to 1.1 x 10 -3 , which is the frequency of appearance of hybrid seedlings that overcame lethality in a previous study of the N. tabacum x N. africana cross 18 .…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…Speci cally, 11 hybrid seedlings that had overcome lethality were obtained, and the frequency of appearance of hybrid seedlings that overcame lethality in this cross combination was calculated to be 8.5 x 10 -4 . This value was close to 1.1 x 10 -3 , which is the frequency of appearance of hybrid seedlings that overcame lethality in a previous study of the N. tabacum x N. africana cross 18 .…”
Section: Discussionsupporting
confidence: 80%
“…Additionally, Ma 11 observed that the H chromosome belongs to the S genome. Therefore, we infer that the H chromosome in the reports of Hancock et al 18 and Ma 11 is the same as the Q chromosome in the report of Tezuka et al 17 . If this interpretation is valid, we consider it highly likely that Nt6549g30 is involved in the lethality of the N. suaveolens x N. tabacum cross.…”
Section: Introductionsupporting
confidence: 56%
See 2 more Smart Citations
“…The unique genomic composition of two different parental genomes within one nucleus can lead to intergenomic conflicts such as chromosome elimination. Chromosome elimination has been reported in interspecific hybrids within other crop species genera such as Hordeum (Subrahmanyam and Kasha, 1973) and Nicotiana (Hancock et al, 2015). Hypotheses to explain the mechanisms of chromosome elimination after interspecific hybridization in various crop species include differences in timing of the mitotic cycle between the two species, histone changes resulting in the failure of centromeres to attach to the spindle microtubules, host‐specific nucleases capable of degrading alien chromatin, or the formation of micronuclei followed by selective removal (Kasha and Kao, 1970; Subrahmanyam and Kasha, 1973; Finch, 1983; Gernand et al, 2005; Ravi and Chan, 2010, 2013).…”
Section: Discussionmentioning
confidence: 99%